2018
DOI: 10.1177/0020764018776349
|View full text |Cite
|
Sign up to set email alerts
|

The effect of loneliness on depression: A meta-analysis

Abstract: According to the results of the research, loneliness may be said to be a significant variable affecting depression. The findings obtained are discussed in light of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
333
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 536 publications
(380 citation statements)
references
References 71 publications
39
333
1
7
Order By: Relevance
“…Women reported feelings of loneliness more often than men, as has been found earlier [41], but the association with psychological distress was equal in both genders. Previous studies have shown that loneliness is a signi cant risk factor for depression [94] and other common mental disorders [43] as well as for suicidal ideation and suicide attempts [95]. Furthermore, loneliness is associated with an increased risk of many health problems [95], and it has been increasingly seen as an important public health problem [96].…”
Section: Discussionmentioning
confidence: 99%
“…Women reported feelings of loneliness more often than men, as has been found earlier [41], but the association with psychological distress was equal in both genders. Previous studies have shown that loneliness is a signi cant risk factor for depression [94] and other common mental disorders [43] as well as for suicidal ideation and suicide attempts [95]. Furthermore, loneliness is associated with an increased risk of many health problems [95], and it has been increasingly seen as an important public health problem [96].…”
Section: Discussionmentioning
confidence: 99%
“…Women reported feelings of loneliness more often than men, as has been found earlier [41], but the association with psychological distress was equal in both genders. Previous studies have shown that loneliness is a signi cant risk factor for depression [91] and other common mental disorders [43] as well as for suicidal ideation and suicide attempts [92]. Furthermore, loneliness is associated with an increased risk of many health problems [92], and it has been increasingly seen as an important public health problem [93].…”
Section: Discussionmentioning
confidence: 99%
“…Three meta-analyses focused on studies with children and adolescents. [28][29][30] The included meta-analyses based on cross-sectional designs reported a significant positive association between social isolation and late-life suicidal ideation, 31 depression in adults, 32 late life depression, 26 psychosis, 28,33,34 smoking behavior in adolescents, 29 depression and social anxiety in childhood and adolescence, 28,30 and social anxiety disorder in adults. 35 The meta-analyses based on longitudinal studies suggest that social isolation is associated with higher risk of depression in adults, 36 post-acute coronary syndrome depression, 37 and dementia and cognitive impairment in later life.…”
Section: Selection and Characteristics Of Included Studiesmentioning
confidence: 99%